Emotional, motivational and attitudinal consequences of autonomous prosocial behaviour. (8th November 2022) - Kelley, Nicholas J.; Weinstein, Netta; Smith, Emily E.; Davis, William E.; Christy, Andrew G.; Sedikides, Constantine; Schlegel, Rebecca J.
Abstract: When do prosocial actors experience positive versus negative psychological outcomes from helping others? In four studies and an internal meta‐analysis, we tested the hypothesis that autonomy shapes the psychological consequences of helping others. In Study 1, prosocial behaviour was associated with a robust pattern of negative well‐being outcomes (i.e., depression, anxiety, stress) for individuals low but not high in autonomy. In Studies 2–4, relative to reflecting on a neutral interpersonal experience, reflecting on an autonomous helping experience increased sadness and happiness, strengthened intentions to help in the future and raised support for social welfare. By contrast, reflecting on a controlled helping experience increased negative emotions and decreased positive emotions, but did not affect attitudes or behavioural intentions. Collectively, the findings indicate that autonomy (or lack thereof) shapes the emotional, motivational and attitudinal consequences of helping behaviour.